(untitled) (Innovation & Development in Engineering and Applied Science, 2026)
Software-defined networking (SDN) requires efficient controllers to manage time-sensitive traffic, yet there is limited evidence on their comparative performance under demanding load conditions. This study evaluates three widely used SDN controllers: OpenDaylight (ODL), ONOS, and Ryu, under three load scenarios (low, medium, and high) in an emulated Mininet environment. Latency, jitter, throughput, packet loss, availability, and memory consumption were measured during multimedia streaming transmission. The results show that Ryu maintains the best balance between service continuity and effective delivery as concurrency increases, exhibiting lower degradation in availability and throughput. ONOS delivers competitive performance with an emphasis on high availability, whereas ODL is more sensitive to increased load, particularly in delivery-related metrics. The study concludes that controller selection should prioritize service continuity and delivery reliability in high-concurrency scenarios.